2020
DOI: 10.21203/rs.3.rs-77801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale, enzyme-based xenobiotic identification for exposomics

Abstract: Advances in genomics have revealed many of the genetic underpinnings of human disease, but exposomics methods are currently inadequate to obtain a similar level of understanding of environmental contributions to human disease. Exposomics methods are limited by low abundance of xenobiotic metabolites and lack of authentic standards, which precludes identification using solely mass spectrometry-based criteria. Here, we develop and validate a method for enzymatic generation of xenobiotic metabolites for use wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Although current efforts are focused on generating spectral libraries of unknown metabolites, these methods have not been extended to GC-HRMS. (29,32) The limited annotation of environmental chemicals associated with PSC underscores a major challenge in gaining biological insight using untargeted GC-HRMS and the need for improved annotation tools for exposome research. This chemical, terbucarb, is a carbamate pesticide, a class of insecticide widely used in household, agricultural, and industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…Although current efforts are focused on generating spectral libraries of unknown metabolites, these methods have not been extended to GC-HRMS. (29,32) The limited annotation of environmental chemicals associated with PSC underscores a major challenge in gaining biological insight using untargeted GC-HRMS and the need for improved annotation tools for exposome research. This chemical, terbucarb, is a carbamate pesticide, a class of insecticide widely used in household, agricultural, and industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed dihydroxybupropion in mice following oral gavage of bupropion (Fig. 4A), and in a plasma sample from a patient with documented bupropion use in which we had previously identified hydroxybupropion and hydrobupropion (Liu et al, 2021). The retention times and ion fragmentation spectra for dihydroxybupropion detected in the patient matched that of the CYP2B6 generated dihydroxybupropion (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…We have previously shown that S9 enzymes can be used to provide a high-throughput approach to generate Phase I and II metabolites to identify xenobiotic exposures in humans (Liu et al, 2021). The P450 cell lines provide a complementary workflow for simultaneous generation of Phase I, CYP-dependent, metabolites of xenobiotics, and subsequent identification of active enzyme-substrate pairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRMS analyses follow established protocols using dual liquid chromatography-ultrahigh-resolution mass spectrometry (LC-MS) for metabolomics and gas chromatography-ultrahigh-resolution mass spectrometry (GC-MS) for exposomics with data extraction supporting both targeted and untargeted analyses [28,29]. Capabilities can identify a very broad spectrum of endogenous metabolites, food and microbiome metabolites, and environmental chemical exposures [28,29].…”
Section: Biological Specimen Collection For Crp and Multi-omics Studiesmentioning
confidence: 99%